2021
DOI: 10.1016/j.rssm.2020.100543
|View full text |Cite
|
Sign up to set email alerts
|

Does downward social mobility make people more hostile towards immigrants?

Abstract: This study explores the relationships between intergenerational social class mobility and attitudes towards immigration. We interpret a failure to keep up with parental social class (i.e. downward mobility) as an indicator that individual's status achievements lag behind expectations and contribute to subjective feelings of loss and decline. An innovative feature of this study is that we investigate both whether individual's mobility experience-micro-level-and also whether opportunity structuresmobility on a m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
1
14
0
1
Order By: Relevance
“…Subjective data are an important complement to conventional status indicators and may detect trends not reflected in these measures. Lived mobility experiences matter in their own right but also as an implicit component in models of how socioeconomic factors influence attitudes, behavior, and well-being (Chan 2018; Gugushvili 2020; Kaiser and Trinh 2019; Newman 1999; Paskov, Präg, and Richards 2020). Not least is this evident in recent discussion of the precipitous rise in “deaths of despair” associated with alcohol, drugs, and self-harm.…”
mentioning
confidence: 99%
“…Subjective data are an important complement to conventional status indicators and may detect trends not reflected in these measures. Lived mobility experiences matter in their own right but also as an implicit component in models of how socioeconomic factors influence attitudes, behavior, and well-being (Chan 2018; Gugushvili 2020; Kaiser and Trinh 2019; Newman 1999; Paskov, Präg, and Richards 2020). Not least is this evident in recent discussion of the precipitous rise in “deaths of despair” associated with alcohol, drugs, and self-harm.…”
mentioning
confidence: 99%
“…Yet, there are limits to which cities our findings can be extended. Previous research shows that context influences both multicultural attitudes (Leong and Ward 2006) and the consequences of social mobility on, for instance, attitudes towards immigration (Paskov et al 2020). It is for future research to investigate how macro effects shape the association between the experience of social mobility and multicultural attitudes.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, our research adds to an already existing body of empirical work showing that the experience of downward social mobility is multi-faceted and can play out in different ways in different domains of social life, more precisely when it comes to positive or negative attitudes towards immigrants. While downward mobility might lead to more negative attitudes towards highly specific aspects of inter-ethnic attitudes (for instance, inter-ethnic marriage, as Tolsma et al show [2009]) others have not found any negative effects of downward mobility on migration issues overall (Paskov et al 2020;Stawarz and Müller 2020;Tolsma et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the connection between upward mobility and left voting lacks empirical support. 2 Some studies do not find evidence for a positive relation between the former and pro-redistribution preferences (Jaime-Castillo and Marqués-Perales 2019), cultural liberalism (Paskov et al 2020), or voting for left parties (Kurer and van Staalduinen 2020). 3 Even more strikingly, other studies find just the opposite: upward mobility appears to increase economic conservatism (Alesina and La Ferrara 2005;Ares 2020;Corneo and Grüner 2002;Piketty 1995;Siedler and Sonnenberg 2012) and right-wing voting (Abramson and Books 1971;Breen 2001), at least among some groups (Mayer and Perrineau 1992).…”
Section: Voting In the Golden Age Of Capitalismmentioning
confidence: 99%
“…On the one hand, the argument that upwardly mobile citizens disproportionately support inequality reduction and cultural progressivism is not corroborated by empirical evidence (Abramson and Books 1971;Alesina and La Ferrara 2005;Ares 2020;Breen 2001;Corneo and Grüner 2002;Jaime-Castillo and Marqués-Perales 2019;Piketty 1995;Siedler and Sonnenberg 2012). On the other, although the claim that dissatisfaction stemming from downward mobility favours radical voting has received some support (Daenekindt et al 2018;Mayer 2002;Peugny 2006), it remains unclear whether this is most relevant for parties on the left or the right (Kurer and van Staalduinen 2020;Mitrea et al 2020) and why (Paskov et al 2020;Tolsma et al 2009).…”
Section: Introductionmentioning
confidence: 99%